KV. Cohomology and some applications - Ferdinand, Ngakeu (My University, 2020)
Two versions of the KV-cohomology are presented and some algebraic and geometrical applications are given. We will see some applications to stochastic manifold. As a consequence, we can apply these ideas in Lorentzian geometry, in particular in the theory of null hypersurfaces where it is defined a non Levi-Civitta connection as an auxiliary tool, and so, there is a stochastic structure.
Keywords: Álgebra; Geometría; KV-Cohomología